OLMSTED, DE BOW, AND THE WEIGHT OF EVIDENCE ON THE AMERICAN SLAVE SOUTH. Issue 2 (1st June 2015) - Maas, Harro
Abstract : Scholarship on the American Slave South generally agrees that John Eliot Cairnes's The Slave Power provided a highly biased interpretation of the functioning and long-term viability of the southern slave economy. Published shortly after the outbreak of the Civil War, its partisanship is partly attributed to its clearly stated goal to shift British support from the secession states to the states of the Union. Thus, it is generally agreed, Cairnes sifted his sources to obtain the desired outcome. A more balanced use of the sources at his possession would have provided a very different outcome. This paper will challenge this general assessment of Cairnes's book by examining in some detail two of Cairnes's most important sources: Frederic Law Olmsted's travelogues on the American Slave South and James D. B. De Bow's compilation of statistical data and essays in his Industrial Resources, etc., of the Southern and Western States (1852–53). By contrasting De Bow's use of statistical evidence with Olmsted's travelogues, my final purpose is to question the weight of evidence on the American Slave South. Cairnes aimed, I will argue, much more to balance the evidence than is generally acknowledged, but it is misleading to think that balancing a wide range of evidence washes out bias if this evidence itself is politically skewed, as is the rule rather than the exception.